(untitled) (International Journal of Engineering and Computer Science, 2018)
Education is one of the major sectors for national development, being given serious attention on increasing educational organizations geographically, increasing literacy rate i.e. to cover more and more human resource of the country and elevating the level and improving quality of education as well as spreading more education to the society. The speed of change brought by new Science & Technologies had an important outcome on the way people live, work, and plays worldwide. New and emerging Science & Technologies challenge the traditional process of teaching and learning, and the way education is managed. Science & Technology, while an essential area of study in its own right, is having a key impression across national curriculum areas. There has been an exceptional growth in the use of science and technology in teaching, research and extension activities. This paper is an endeavor to assess the extent trend of students for Science and Technology (S&T) education and Arts & Commerce (A&C) education in various years of study from 2011 to 2014. Current attention is being paid on the practical application of education in field’s science, engineering, architecture, medical, information & communication technology, agriculture, Social science, commerce, geography commerce and others which comes under these major disciplines